Duration Aftereffect Depends on the Duration of Adaptation - Li, Baolin; Xiao, Lijuan; Yin, Huazhan; Liu, Peiduo; Huang, Xiting (Frontiers in Psychology, 2017)
It has been widely demonstrated that a prolonged adaptation to a relatively long or short stimulus leads to a robust repulsive duration aftereffect. However, little is known about the rapid adaptation to stimulus duration. In this study, we investigated whether the duration aftereffect could also be induced by short-term adaptation to stimuli of both sub- and supra-second durations. To control for the internal reference for duration judgment, participants were adapted to a stimulus of medium duration, and then tested with both longer and shorter stimuli. We found that the duration aftereffect was only observed after long-term adaptation to stimuli of both sub- and supra-second durations, which suggests that the exposure time to the adaptor is a fundamental factor in determining the duration aftereffect. Our findings offer further evidence of the duration aftereffect, which in this study was dissociated from the anchor effect and high-level aftereffects.